METHODS OF USING NETWORK TECHNOLOGIES IN THE PROCESS OF INDIVIDUAL EDUCATION - Shokhrukhbek Yuldoshev (European Science Publishing, 2024)
The integration of network technologies into individual learning has made learning a more convenient, flexible and personalized process. Through online learning platforms, flexible technologies, virtual classrooms and collaborative tools, students can engage in learning that suits their individual needs. This article presents several ways to use network technologies in the process of individual learning.
Keywords: Online learning platforms, flexible learning technologies, online tutoring and virtual classrooms, collaborative learning tools, educational programs and tools, virtual and augmented reality (VR/AR) in education.